INTERPERSONAL COMMUNICATION STRATEGY OF PERFUME CONSULTANTS IN BUILDING BUYER TRUST AT LAB ART MEDAN - Amanda Yasminta; Kasron Nasution (Journal Analytica Islamica, 2026)
This study aims to analyze the interpersonal communication strategies used by perfume consultants to build customer trust at Lab Art Medan. The study employed a descriptive qualitative approach, with data collection techniques including in-depth interviews, observation, and documentation. Three purposively selected informants were selected: the store manager, a perfume consultant, and a customer who had previously participated in a consultation at Lab Art Medan. The results indicate that customer trust is built through a dialogic two-way communication pattern, a personal approach to understanding customer needs, communicative perfume education, and the creation of a comfortable and participatory shopping experience. These strategies enable customers to not only obtain product information but also experience a more personal, relevant, and convincing interaction during the purchasing process. These findings confirm that interpersonal communication functions not merely as a promotional tool but also as a relational mechanism that builds trust and differentiates Lab Art Medan from other, more transaction-oriented perfume stores. Scientifically, this study contributes to enriching the study of interpersonal communication in the context of consultation-based retail services, particularly in the perfume industry, which is heavily influenced by subjective consumer preferences.